LinguaForum TOEFL iBT test book I : (Tổng hợp Thành phố Hồ Chí Minh, 2006)
This book contains two full identical format practice tests for the TOEFL (Test of English as a Foreign Language) iBT exam and four high quality audio CDs for the listening and speaking sections, designed to prepare students for the exam. This practice tests simulate the computer testing environment with test sequences, questions and format. Also provided are newly introduced speaking and writing sections of the new Next Generation TOEFL and detailed information about the new iBT TOEFL. With Test Book 1, test takers can not only familiarize themselves with the format of the test, but also gain valuable insights into how to improve their scores.